EARNINGS MANAGEMENT: THE CASE OF LUCENT TECHNOLOGIES - Faissol Janot de Matos, Felipe; Sancovschi, Moacir (Revista Universo Contábil, 2007)
The use of accounting discretion to window dress financial statements seems to be eroding public confidence in the financial reporting process. Critics argue that some managers are intentionally abusing GAAP’s afforded discretion to manage earnings. This can reduce the quality of the financial reporting process and ultimately bring adverse effects on resource allocation in the economy. Not surprisingly, market participants, legislators, regulators, and academics are concerned with the need to control financial reporting abuses. In this paper we briefly review the recent literature on earnings management and show the incentives as well as the mechanics used by Lucent’s managers to manipulate earnings. We found strong incentives for Lucent’s managers to report smooth and increasing earnings to: a) increase the firm’s market capitalization; b) enhance management compensation and job security; and c) reduce the company’s cost of capital. The evidence we found suggests that the managers used: a) big bath restructuring charges; b) miscellaneous cookie jar reserves; c) premature and aggressive revenue recognition; and d) creative acquisition accounting and purchased R&D to manage earnings. Keywords: Financial statements. Manipulate earnings. Managers.